Improving patient outcomes with regorafenib for metastatic colorectal cancer - patient selection, dosing, patient education, prophylaxis, and management of adverse events - Hofheinz, Ralf-Dieter (Oncology research and treatment, 2015)
Regorafenib is the first tyrosine kinase inhibitor approved for metastatic colorectal cancer. In 2 phase III trials, regorafenib significantly improved progression-free and overall survival in patients who had been previously treated with fluoropyrimidine-, oxaliplatin-, and irinotecan-based chemotherapy, an anti-vascular endothelial growth factor therapy, and, if (K)RAS wild type, an anti-epidermal growth factor receptor therapy. Its safety profile is in line with other multikinase and/or tyrosine kinase inhibitors approved for different indications. Commonly reported adverse events specifically associated with regorafenib include hand-foot skin reaction and hypertension, whereas others such as fatigue, diarrhea, and liver dysfunction may occur during both targeted and cytotoxic treatments. These adverse events frequently occur within the first cycles of treatment, are transient, and decrease in incidence over time. Patient selection, education, and management, as well as close communication between oncologists or trained nurses and patients, are essential for prevention and mitigation of treatment toxicity as is rapid implementation of dose modifications and temporary discontinuations. Effective management of adverse events enables patients who are responding to stay on treatment for a substantial period of time and thereby receive the full benefit of regorafenib therapy. This review aims to provide guidance around prophylaxis and management of regorafenib-associated adverse events.